Fraud Prevention Model in Sharia Financial Institutions in Medan City - Pradesyah, Riyan; Rahmayati; Khairunnisa (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Fraud in Islamic financial institutions remains a concerning issue despite their strong normative foundation in ethical and religious values. Emerging evidence suggests that structural and psychosocial pressures, such as lifestyle and organizational culture, may override personal religious values in influencing fraudulent behavior. Purpose: This study aims to analyze the direct and indirect influence of religiosity, work environment, and lifestyle on fraud behavior among employees of Islamic financial institutions, with social climber behavior as a mediating variable. Design/Methodology/Approach: Using a quantitative approach, data were collected from 160 respondents selected based on purposive sampling. The analysis employed Structural Equation Modelling (SEM) with SmartPLS 3.0 software to test the proposed hypotheses and examine both direct and mediated effects. Findings/Result: This study indicates that religiosity does not affect fraudulent behavior or social climbing. A healthy work environment suppresses deviant behavior, while a consumptive lifestyle increases it. Additionally, social climbing serves as a mediator linking the influence of the work environment and lifestyle on fraudulent behavior. Conclusion: Structural and psychosocial variables play a more substantial role in predicting fraud compared to personal religiosity, which appears insufficiently internalized to deter unethical conduct. Organizational policies should thus prioritize adaptive control systems, lifestyle management, and early psychosocial assessments in fraud prevention. Originality/Value: This study extends the Fraud Triangle Theory by integrating the social climber construct and testing its mediating role. It provides a nuanced understanding of how symbolic social pressures can drive fraud in Islamic financial contexts, offering practical implications for risk mitigation strategies beyond conventional religious approaches. Keywords: work environment, fraud behavior, lifestyle, religiosity, social climber